Constraints on the usage of verbal negation in Brazilian portuguese– Evidence from a spoken corpus - Lima e Silva, Luis Filipe (Universidad de Costa Rica. Campus Rodrigo Facio. Sitio web: https://www.ucr.ac.cr/ Teléfono: (506) 2511-4000. Correo de soporte: revistas@ucr.ac.cr, 2017)
The verbal negation system of Brazilian Portuguese (BP) presents three forms: preverbal, double and postverbal negation, as can be seen in the following examples: *MIC: [91] mas / Michael / eunãofalonessesentido // (ii) *DOM: [101] cêsnũlêemissomaisnão // (iii) *RUT: [220] participanão / minhafilha //. The purpose of this paper is to investigate whether there is any kind of prosodic-informational restriction to the distribution and use of the above-mentioned negation forms in BP through the spontaneous speech corpus C-ORAL-BRASIL BRASIL (Raso& Mello, 2012). Through the analysis of the data collected from C-ORAL-BRASIL, we propose that double and postverbal negation can only occur in illocutionary information units (COM, CMM, COB), whereas preverbal negation has free distribution, occurring in both illocutionary and non-illocutionary textual units. This indicates that non-canonical negation forms depend on illocutionary force in order to be fully realized.